The Occurrence of Occult Acetabular Dysplasia in Relatives of Individuals With Developmental Dysplasia of the Hip. Issue 1 (January 2016) - Carroll, Kristen L.; Schiffern, Alison N.; Murray, Kathleen A.; Stevenson, David A.; Viskochil, David H.; Toydemir, Reha; MacWilliams, Bruce A.; Roach, James W.
Abstract : Background: This study sought to determine the hip pathology of family members of patients with developmental dysplasia of the hip (DDH). The authors evaluated 120 people from 19 families known to have at least 1 member with surgically treated DDH. Each individual's functional outcome scores and pelvic radiographs were assessed for hip symptoms or pathology. Methods: Using a genetic population database and a pediatric hospital patient population, 19 families with high rates of DDH were identified. All family members (n=120) underwent physical examination, radiographic assessment, and completion of outcome instruments [American Academy of Orthopedics (AAOS) Hip and Knee; Harris Hip Score (HHS); and Western Ontario and McMaster Universities Arthritis Index (WOMAC)]. Results: The 120 subjects ranged from 1 to 84 years, 34 had orthopaedically treated DDH. Of the remaining 86 supposedly normal subjects, 23 (27%) had occult acetabular dysplasia (OAD) as defined by center edge angle (CEA) <20 and/or a Severin score of III or greater. Sixty percent of the 86 individuals were less than 30 years old, 74% of the OAD group were less than 30. Outcome scores of the treated DDH patients (AAOS, HHS, and WOMAC) were worse on the involved side regardless of age. Over age 30 individuals with OAD had statistically significant decreases in their AAOS Hip and Knee and WOMAC scores on the dysplastic side, but their HHS scores were not significantly different. Conclusions: Twenty-seven percent of first-degree and second-degree relatives of patients with DDH had unsuspected radiographic acetabular dysplasia in our study. Most of the subjects with OAD were younger than 30. After age 30, many of these patients developed symptoms. Clinical Relevance: In families with a significant history of DDH, radiographic screening of siblings of patients with DDH to define OAD may be prudent. Level of Evidence: Level I—diagnostic study.